2008
DOI: 10.1210/jc.2007-2454
|View full text |Cite
|
Sign up to set email alerts
|

Normal Values of Circulating Insulin-Like Growth Factor-I Bioactivity in the Healthy Population: Comparison with Five Widely Used IGF-I Immunoassays

Abstract: We established age-specific normative values for the IGF-I KIRA. We observed a significant drop in IGF-I bioactivity in women between 50 and 60 yr, which was not perceived by IGF-I immunoassays. The IGF-I KIRA, when compared with IGF-I immunoassays, theoretically has the advantage that it measures net effects of IGF-binding proteins on IGF-I receptor activation. However, it has to be proven whether information obtained by the IGF-I KIRA is clinically more relevant than measurements obtained by IGF-I immunoassa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 24 publications
3
44
2
1
Order By: Relevance
“…Our data support this finding because we found that IGFBP1 significantly and negatively predicted bioactive IGF1 in multiple linear regression analysis. Although this regression analysis did not identify total IGF1 as a significant predictor of bioactive IGF1, we found that total and bioactive IGF1 were closely related in a correlation analysis and other studies have also demonstrated the positive associations between immunoreactive IGF1 and bioactive IGF1 (23,33).…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Our data support this finding because we found that IGFBP1 significantly and negatively predicted bioactive IGF1 in multiple linear regression analysis. Although this regression analysis did not identify total IGF1 as a significant predictor of bioactive IGF1, we found that total and bioactive IGF1 were closely related in a correlation analysis and other studies have also demonstrated the positive associations between immunoreactive IGF1 and bioactive IGF1 (23,33).…”
Section: Discussioncontrasting
confidence: 94%
“…In contrast to our observations, Brugts et al observed higher levels of bioactive IGF1 in females compared with males until the age of 55 years, whereafter bioactive IGF1 decreased markedly in females resulting in higher levels in males. A decline in bioactive IGF1 related to the menopause was suggested (23). This age-related decrease in bioactive IGF1 in females was not accompanied by a decrease in total serum IGF1 levels.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In our laboratory, we have developed three bioassays, specific for the human IR-A, the human IR-B and the human IGF1R, which quantify ligand-stimulated phosphorylation of tyrosine residues within the specific receptors (Brugts et al 2008, Varewijck et al 2010. These assays use human embryonal kidney (HEK) cells which are stably transfected with cDNA of either the human IR-A, the human IR-B or the human IGF1R.…”
Section: In Vitro/ex Vivo Cell Culture Systemsmentioning
confidence: 99%
“…Circulating IGF1 bioactivity was measured using an in-house IGF1 kinase receptor activation assay (IGF1 KIRA) as was previously described (10,11). The methodology of this latter assay is based on another principle than that of IGF1 immunoassays.…”
Section: Igf1 Kinase Receptor Activation Assaymentioning
confidence: 99%